Rice Crop Manager Odisha: CGIAR Innovation Packages and Scaling Readiness (IPSR) Innovation Profile - Gakhar, Shalini; Bharti, Preeti (International Rice Research Institute, 2025)
Rice Crop Manager is designed for use by extension workers, crop advisors, input providers, and agricultural service providers who interview farmers using a personal computer, smartphone, or tablet. Collected information is then transmitted via the Internet to the RCM ‘model', which calculates and transmits a crop management guideline for the rice-based cropping system within moments back to the computer, smartphone, or tablet. Each guideline provides an actionable and unique recommendation for the rice crop, which matches the location-specific cropping practices and needs of the farmer.